(untitled) (Fiep Bulletin - online, 2013)
Object: This study aimed to evaluate the acute effect of maintaining a single GPR stance in the strength and extensibility of the lumbar musculature and compare variables between two postures of the technique, one sitting and one lying.Methodology: This is a clinical trial, non-randomized study, where 20 women were divided into group 1 (G1) and group 2 (G2) randomly. These were subjected to a posture of RPG ’’frog in the air’’ and ’’sitting at the center’’, respectively. The subjects were assessed prior to the posture immediately after and within 24 hours. The variables analyzed were extensibility, through the Wells Bench and muscle strength of the lumbar spine, dorsal through a dynamometer.Results: As for extensibility in the seated position, it increased significantly immediately after laying GPR (p value 0.01131) and after 24 hours of therapy (p value 0.02219). As for other variables, no significant result. Conclusion: The GPR technique can provide gains extensibility back immediately after a single session, maintaining the effect for 24 hours, when the ’’sitting at the center’’ posture is used.